Health care utilisation and medication one year after myocardial infarction in Germany – a claims data analysis. (1st February 2020) - Ulrich, Raven; Pischon, Tobias; Robra, Bernt-Peter; Freier, Christian; Heintze, Christoph; Herrmann, Wolfram J.
Abstract: Background: After myocardial infarction, guidelines recommend pharmaceutical treatment with a combination of five different types of drugs for prevention in patients. However, studies from different countries have shown that this goal is not achieved in many patients. The aim of this study was to assess both healthcare and prescribed pharmaceutical treatment in the fourth quarter after index myocardial infarction. Methods: We conducted a claims data analysis with the data of patients who had had a myocardial infarction in the years 2013 or 2014, using information from the largest German health insurance fund ('AOK'). We analysed contact with physicians, hospital care and actual prescriptions for medication recommended in international guidelines, referring to beta-blockers, ACE inhibitors or angiotensin II receptor blockers, P2Y12-antiplatelet agents, acetylsalicylic acid and statins, one year after myocardial infarction. Analysis was stratified by age and sex, compared between patient groups and over time. Results: We identified 2352 patients who had survived myocardial infarction. Some 96.9% of these participants had at least one contact with their general practitioner (GP) one year after myocardial infarction, 22.8% contacted a cardiologist and 19.7% were hospitalised. Prescription rates range from 37.8% for acetylsalicylic acid to 70.4% for ACE inhibitors. However, only 24.1% received statins, beta-blockers, ACE inhibitors and an antiplatelet drug simultaneously. Prescription of recommended drugs after myocardial infarction decreased steadily over time. Discussion: Long-term medical prevention after myocardial infarction is improvable. GPs should take care of the pharmaceutical prevention after myocardial infarction as they are the physicians seen most intensively in this period. Graphical abstract: Health care utilisation and pharmaceutical treatment of patients in the fourth quarter after myocardial infarction. Unlabelled Image Highlights: Nearly all patients see their GP one year after myocardial infarction (MI). Prescription of recommended drugs after MI decreases steadily over time. 24% of patients receive drugs from every drug group one year after MI. Elderly patients and women are most prone to under-provision.